Edukasi Generasi Berencana (Genre) dalam Mengatasi Pernikahan Dini di Kecamatan Kutalimbaru Kecamatan Deli Serdang - Beby Masitho Batubara; Rehia Karenina Isabella Barus; Syafruddin Ritonga (Universitas Medan Area, 2022)
Early-age marriage. Kutalimbaru sub-district Deli Serdang district is one of the sub-districts in North Sumatra with a fairly high number of early marriages, based on information from the village government and the community, early marriage continues to increase from year to year, in 2020 the number of early marriages in Kutalimbaru District Deli Serdang Regency reached 41.34%. The factors that cause the high number of early marriages in Kutalimbaru District include media factors, the average parent in Kutalimbaru District cannot use smartphones, The low level of education in using media for most parents causes them to be unable to assist their children to use technology. according to age. Parents also do not supervise the education and socialization of children. Economic factors are also one of the causes of early marriage, marriage is the main solution, especially for young women to continue their life stage and no longer be a burden on the family. North to be able to actualize the Generation Planning (GenRe) program which is one of the population control programs with the target of teenagers to prepare family life for teenagers and this program invites teenagers to avoid early marriage and premarital sex.